2022
DOI: 10.1039/d2nj01993k
|View full text |Cite
|
Sign up to set email alerts
|

Well-constructed approach of exceptionally water-stable (mesoporous SiO2)-on-(microporous Cu-BTC) composite for efficient methylene blue capture

Abstract: Cationic methylene blue (MB) capture with classical Cu-BTC is definitely restricted and challenged by its water instability issue. Thus the structural stability of Cu-BTC in presence of moisture is a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The pseudo-second-order model (eq S2) assumes that the adsorption rate is regulated by chemical interactions . The Dumwald–Wagner (eq S3) and Weber–Morris intraparticle diffusion models (eq S4) are used to study and describe the channel diffusion and rate control steps during adsorption. , The formulas for the four adsorption kinetic models are given in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pseudo-second-order model (eq S2) assumes that the adsorption rate is regulated by chemical interactions . The Dumwald–Wagner (eq S3) and Weber–Morris intraparticle diffusion models (eq S4) are used to study and describe the channel diffusion and rate control steps during adsorption. , The formulas for the four adsorption kinetic models are given in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, the coefficient of determination ( R 2 ) of the pseudo-second-order model is higher than those of the other models, implying that chemisorption is the major rate-limiting step, which can include sharing of electrons and π–π stacking interactions. Additionally, the Dumwald–Wagner model has a high R 2 , probably because of the mesoporous structure of SiO 2 in the composite nanoparticles . Moreover, the Weber–Morris intraparticle diffusion model was used to study the diffusion mechanism and primary rate-controlling steps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through comparing and observing the XRD pattern of Fig. 3(a), Cu-BTC has characteristic diffraction peaks at (220), ( 222), (400), (422), (333), (440), and (422), corresponding to the references (Dong et al, 2022). Material Studio 7.0 was also explored by us to simulate the theoretical XRD graphs of the samples.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…23,24 The coordination bonds of Cu 2+ and BTC are very likely destroyed by coming in contact with water molecules, causing an irreversible collapse. 25 Li et al studied the adsorption performance of Cu-BTC from the dibenzothiophene/isooctane model oil system of water-bearing molecules and found that when the water content was 4 wt%, the pore structure of the material collapsed rapidly, and the adsorption capacity was reduced by 86%. 26 Some strategies have been investigated to boost the water stability of Cu-BTC through grafting hydrophobic groups, wrapping with hydrophobic film, doping with carbon, etc.…”
Section: Introductionmentioning
confidence: 99%